A construção da comicidade em textos da dramaturgia de Plínio Marcos - Silveira, Edson Luiz da (2016)
The subject of our work is the presence of comicability in dramatic texts. The laughter is an ability that finds exclusivity in man’s spirit ( mind), but not always the one who laughs knows the first reason of his laughter, and not always this same laughter appears in contexts where it is expected (waited). Our goal, therefore, is to try to understand how the mechanism of comicability is processed in the plays of Plínio Marcos, a playwright born in Santos, Brazil, once his works are not considered as traditional comedies by the criticism. We used as corpus of this research nine of the author’s plays, which we consider more relevant to get to our hypothesis that the humor in dramaturgy doesn’t restrain to the known comedies, for, even not been classified as comedy, while reading Plínio Marcos’s dramatic texts, we are taken to laughter, although many times we even don’t know why. To prove our intent, we relied, among others, on the French author Henri Bergson’s studies and his work The Laughter served as a bigger basis to the research, due to the agreement of its corpus with ours – both texts about dramaturgy, although Bergson has focused on the French comedies. As analysis methodology we applied resources and concepts already developed by Bergson and other authors, while we thought it possible to apply them to Plínio Marcos’s plays too. Based on our analysis we could confirm that comicability and laughter may appear in determinate situations where at first they are not expected (waited) and this is due to the fact that laughter and comicability are part of categories related to the man, much more than to any formal genre of textual structures, and also due to Plínio Marcos’s ability of building his dialogues in so spontaneous way, so close to orality and so connected to man’s first nature